Design of functionally graded joints using a polyurethane-based adhesive with varying amounts of acrylate. (July 2017) - Stapleton, Scott E.; Weimer, Julia; Spengler, Jan
Abstract: Adhesives with graded properties along the bondline are being developed to increase the strength of adhesively bonded joints. Efforts to do this in the past have resulted in mixed results. Two adhesive parameters need to be considered: the geometry of the gradation and the material properties of the adhesive at different gradation levels. In order to consider both of these aspects, a computational model was created to aid in not only the design of adhesive gradations but also judge whether a specific adhesive gradation method will be able to result in strength increases. In this study, the model was introduced and compared with published results. A new adhesive gradation system was created by using a polyurethane-based adhesive with varying amounts of acrylate, and a numerical analysis was performed to determine the potential advantages of the adhesive gradation.